EFEKTIVITAS RAZIA KENDARAAN DALAM MEMBENTUK KESADARAN HUKUM MASYARAKAT - Adi Syahputra Sirait (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2020)
This paper aims to analyze and explain the effectiveness of the implementation of the Raids of Kenderaan carried out by the Asahan resort police for the legal awareness of the Asahan community in making a SIM (Driving License) and Vehicle Tax. This paper uses an empirical normative method with a social legal research approach, the data used in this paper are data from the Kiaaan Raid conducted by the asahan resort police since 2017-2019, data on SIM issuance and management of the Kenderaan Tax, data collection is done through interviews and documentation, then the data is analyzed so that conclusions are born. The Assault Raid conducted by Asahan Regional Police showed that there was a significant influence on the number of people who made SIMs and administered the Vehicle Tax, so that the conclusion was drawn that the Assault Raid was very effective in increasing public legal awareness in curbing the vehicle documents.